The Capacity of Leaders in Interpreting and Implementing Human Resource Policies From The Central Level - Happy Chriesnita Sari Guna; Jajang Gunawijaya (Syntax Literate, 2023)
This study aims to uncover and analyze the values of the personal dimensions of employees of Askrindo East Jakarta Branch are related to self-development in improving its performance. The research method used is qualitative analysis with an ethnographic approach. The problem to be answered is obtained through observation and in-depth interviews with participants or research informants consisting of leaders and employees of PT. Askrindo East Jakarta Branch which is directly related to the research subject so that conclusions can be drawn following the actual conditions. The study found that there was a very high tendency towards the characteristics of result orientation in the culture of PT. Askrindo. The result orientation refers to a very high tolerance caused by the family culture brought by the organization from the beginning of the company's establishment. The basic assumption of PT. Askrindo East Jakarta Branch is the basic assumption of maturity, which is identical to groupism according to Schein's model. This assumption makes PT. Askrindo East Jakarta Branch became comfortable and reluctant to carry out cultural development beyond what had been outlined by PT. Askrindo is the central company.